2022
DOI: 10.1021/acsami.2c00616
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Bi2O2Se/Bi2Se3 Van Der Waals Heterostructures for Self-Powered and Broadband Photodetectors

Abstract: Due to its superior carrier mobility and high air stability, the emerging two-dimensional (2D) layered bismuth oxyselenide (Bi 2 O 2 Se) nanosheets have attracted extensive attention, showing great potential for applications in the electronic and optoelectronic fields. However, a high mobility easily leads to a high dark current, seriously restricting optoelectronic applications, especially in the field of photodetectors. In this paper, we report a high-quality Van der Waals (vdWs) Bi 2 O 2 Se/Bi 2 Se 3 hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…The tunneling current cannot be significantly higher than the thermionic current, which results in a stably low bias current of ≈ 6 × 10 –12 A at −4 V condition. On the opposite, the energy band of WS 2 is elevated under a forward bias voltage as shown in Figure d, which allows the electrons to transfer freely from WS 2 to Bi 2 Se 3 , resulting in a relatively high current . Because of the unavoidable surface oxidation of Bi 2 Se 3 , there exists a barrier between the interface, leading the “open” voltage to become slightly shifted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tunneling current cannot be significantly higher than the thermionic current, which results in a stably low bias current of ≈ 6 × 10 –12 A at −4 V condition. On the opposite, the energy band of WS 2 is elevated under a forward bias voltage as shown in Figure d, which allows the electrons to transfer freely from WS 2 to Bi 2 Se 3 , resulting in a relatively high current . Because of the unavoidable surface oxidation of Bi 2 Se 3 , there exists a barrier between the interface, leading the “open” voltage to become slightly shifted.…”
Section: Resultsmentioning
confidence: 99%
“…Then, 2D Bi 2 Se 3 flakes were grown on fluorophlogopite mica substrate by low-pressure physical vapor deposition . The Bi 2 Se 3 powder was placed in the center of the furnace equipped with a quartz tube, and the fluorophlogopite mica substrates were placed downstream 8–11 cm away from the center.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Therefore, it is crucial for device integration to suppress the dark current and decrease the power consumption of Bi 2 O 2 Se-based photodetectors. Designed Bi 2 O 2 Se-based heterojunctions, such as Bi 2 O 2 Se/graphene, Bi 2 O 2 Se/Bi 2 Te 2 Se, Bi 2 O 2 Se/WS 2 , Bi 2 O 2 Se/WSe 2 , and Bi 2 O 2 Se/Bi 2 Se 3 , can address this bottleneck by lowering the dark current and satisfying the specifications of self-powered photodetection, yet it is still challenging for their applications due to the difficulty of large-scale synthesis. Studies have shown that the synthesis of Bi 2 O 2 Se using Bi 2 O 3 and Se as co-evaporation sources , can greatly reduce the residual carrier concentration while ensuring high carrier mobility, which contributes to a very low threshold voltage and low power consumption.…”
Section: Introductionmentioning
confidence: 99%
“… 60 The heterostructure of Bi 2 O 2 Se/graphene was reported for the demonstration of photodetector and short channel FET (50 nm) by Tan et al 61 In another study by Yang et al , Bi 2 O 2 Se/graphene hybrid structure was utilized to demonstrate multifunctional optoelectronics, including photodetector, optical synapse, and logic gate by the control of optical wavelengths. 62 Some recent reports focused on Bi 2 O 2 Se-based heterostructures: Bi 2 O 2 Se/Bi 2 Se 3 , 63 Bi 2 Te 2 Se/Bi 2 O 2 Se, 64 Bi 2 O 2 Se/TMDs, 65 and Bi 2 O 2 Se/CsPbBr 3 , 66 showing potential use of Bi 2 O 2 Se in combination with other materials for optoelectronic applications. Although Bi 2 O 2 Se shows competent light sensing property in a wide band, multifunctional optoelectronic by only the Bi 2 O 2 Se based structure has not been explored so far.…”
Section: Introductionmentioning
confidence: 99%